Principle of Real Estate Management - C. Downs James (American : IREM, 1986)
Contents
1. Dementions of Real estate and its Managment
2. Techniques of real estate managment
3. Scope of real esttate managment
4. Entrepreneurial role of real estate managment
Keywords: Economics; Real Estate Management